Pragmatic approach to qualitative case study research learning by doing a case of distance learning research in Malaysia - Dzakiria, Hisham (Universiti Utara Malaysia, 2008)
This book is for anyone who wants to undertake an engaging, satisfying, productive, and a more successful career as a qualitative researcher. This book is intended to contribute to the popularisation of qualitative research in Malaysia. Qualitative studies in educational research are very limited in many countries; and to date, there has been very little work done using this form of educational inquiry in Malaysia. The dominant tradition has followed the positivist paradigm. A qualitative case study offers a different approach and generates a range of information of different qualities from that obtained using traditional approaches. This book provides both the theories and practical practices to undertake a qualitative study. The conception of this book began from the assumption that our world is interpreted through language as means of communication and understanding. Writing narratives of experience is becoming a common way of describing how people make sense of their experience or problems at hand. At the root of the naturalistic inquiry exhibited in this book, is an interest in understanding the experience of learners and the meanings they make of the distance learning experience at Universiti Utara Malaysia (UUM). This study was designed as a single case focusing on distance learners of different background at UUM. Research like this call for a method that can provide deeper understanding to its inquiry and one that provides validity and understanding of the diversity of views and experiences of the learners on their distance learning programme.